Determinants of Product Purchasing Decisions (Case Study at PT Federal International Finance Branch of Cianjur, West Java): Determinants of Product Purchasing Decisions (Case Study at PT Federal International Finance Branch of Cianjur, West Java) - Hani Fitria Rahmani; Nurus Safa'atillah (Jurnal Mantik, 2020)
This study has the objective to determine how much influence the determinants of the product The purchase decision by Federal Internastional Finance Branch of Cianjur. Known determinants are advertising and brand image. This study used survey method. By spreading the enclosed questionnaire at 74 respondents as consumers of PT Federal International Finance. The research proves there is a direct or indirect effect on advertising on purchasing decisions, and there is a direct or indirect effect on brand image to the purchasing decision. Results further said there are significant research on advertising and brand image together against keutusan the purchase of 92.8%.